Estimation of Carbon Stock of Sediment in Mangrove Ecosystem of Apar Village, North Pariaman Sub-District, West Sumatra - Saputra, Muhammad Nasrul; Nedi, Syahril; Siregar, Yusni Ikhwan (Journal of Coastal and Ocean Sciences, 2025)
Global warming is one of the issues in the world today, characterized by an increase in the earth's temperature due to greenhouse gases. Mangrove forests are one of the blue carbon parameters that can utilize CO2 for photosynthesis and store it in the form of biomass and sediment well. Sediments serve as a growing medium and a place to accumulate various components, including carbon. Carbon stored in mangrove sediments tends to be greater than in other types of forests. The study aimed to determine sediment carbon stocks based on density and the relationship between mangrove density and estimated carbon stocks in sediments in the mangrove ecosystem of Apar Village, North Pariaman District. Mangrove sediment sampling was carried out using the Purpose Sampling technique, and the data obtained were analyzed using the Loss on Ignition method. The results showed that the highest average carbon stock in sediments was found at station 2 with medium density, which was 215,03 tonnes/ha, followed by station 3, which had a high density, with a value of 197,98 tonnes/ha, and the lowest average carbon stock was found at station 1 with medium density, which was 132,43 ind/ha. Future research is expected to observe carbon stocks in mangrove stands and litter in the Apar Village mangrove ecosystem to obtain more detailed information